You better believe I'm gonna talk about it - Rinna, Lisa (Dey St., an imprint of William Morrow, 2026)
Lisa peels back the curtain on her roller coaster career and her unapologetic approach to life, dishing on the highs, the lows, and the unbelievable moments that made her a household name. She's spilling all the tea from the sound stages of Days of Our Lives to the drama of The Real Housewives of Beverly Hills, but she's also opening up about what it means to grow older in an industry obsessed with youth, the lessons she's learned about reinvention, parenting a daughter with a chronic illness, keeping her well-documented marriage alive and healthy, and being forced to grieve in public after the loss of her mother and beloved Beverly Hills fan-favorite, Lois. This is the story of a woman who understands you go the furthest when you set your own rules, who realizes aging is just a new chapter and who isn't afraid to live off script. And shes owning every bit.